Ride-hailing services: Competition or complement to public transport to reduce accident rates. The case of Madrid - Flor, María; Ortuño, Armando; Guirao, Begoña (Frontiers in Psychology, 2022)
Introduction: The transport and mobility sector is experiencing profound transformations. These changes are mainly due to environmental awareness, the increase in the population of large urban areas and the size of cities, the ageing of the population and the emergence of relevant technological innovations that have changed consumption habits, such as electronic commerce or the sharing economy. The introduction of new services such as Uber or Cabify is transforming urban and metropolitan mobility, which has to adapt to this new scenario and the very concept of mobility. Objective: Thus, the purpose of this study was to evaluate whether ride-hailing platforms substitute or complement public transport to reduce accident rates, considering the two basic transport zones of Madrid: “The Central Almond” and the periphery. Methods: The data were collected from the 21 districts of Madrid for the period 2013-2019, and they were analyzed by a Random Effects Negative Binominal model. Results: The results obtained in this study suggest that since the arrival of Uber and Cabify to the municipality of Madrid the number of fatalities and serious injuries in traffic accidents has been reduced. Traffic accidents on weekends and holidays, with at least one serious injury or death, have also been reduced. However, the number of minor injuries has increased in the central districts of Madrid. Conclusion: Overall, what was found in this study supports the hypothesis that these services replace the urban buses. However, these services improve the supply to users with greater difficulties to access taxis or public transport, constituting an alternative mode of transport for high-risk drivers. Therefore, such findings may be quite useful for policy makers to better define regulatory policies for these services.